Massive stars exploding in a He-rich circumstellar medium – VII. The metamorphosis of ASASSN-15ed from a narrow line Type Ibn to a normal Type Ib Supernova. Issue 4 (9th September 2015) - Pastorello, A.; Prieto, J. L.; Elias-Rosa, N.; Bersier, D.; Hosseinzadeh, G.; Morales-Garoffolo, A.; Noebauer, U. M.; Taubenberger, S.; Tomasella, L.; Kochanek, C. S.; Falco, E.; Basu, U.; et al.
Abstract: We present the results of the spectroscopic and photometric monitoring campaign of ASASSN-15ed. The transient was discovered quite young by the All Sky Automated Survey for SuperNovae (ASAS-SN) survey. Amateur astronomers allowed us to sample the photometric SN evolution around maximum light, which we estimate to have occurred on JD = 2457087.4 ± 0.6 in the r band. Its apparent r -band magnitude at maximum was r  = 16.91 ± 0.10, providing an absolute magnitude M r ≈ −20.04 ± 0.20, which is slightly more luminous than the typical magnitudes estimated for Type Ibn SNe. The post-peak evolution was well monitored, and the decline rate (being in most bands around 0.1 mag d −1 during the first 25 d after maximum) is marginally slower than the average decline rates of SNe Ibn during the same time interval. The object was initially classified as a Type Ibn SN because early-time spectra were characterized by a blue continuum with superimposed narrow P-Cygni lines of He i, suggesting the presence of a slowly moving (1200–1500 km s −1 ), He-rich circumstellar medium. Later on, broad P-Cygni He i lines became prominent. The inferred velocities, as measured from the minimum of the broad absorption components, were between 6000 and 7000 km s −1 . As we attribute these broad features to the SN ejecta, this is the first time we have observed the transition of a Type Ibn SN to a Type Ib SN.